Implementasi Single Sign-On Menggunakan Google Identity, REST dan OAuth 2.0 Berbasis Scrum - I Kadek Dendy Senapartha (Maranatha University Press, 2021)
Single Sign-On (SSO) is a technology that can support user convenience in accessing a system. By using SSO, a user only needs to authenticate once to get access to a system. OAuth 2.0 is one of the protocols that can be implemented on the SSO system. Currently, many Application Service Providers (ASP) support the OAuth 2.0 protocol thus providing convenience in the development of a more standard SSO system. Google Identity is one of the services provided by Google that can be used to build SSO systems using the OAuth 2.0 protocol. Application of the request and response methods provided by the protocol specification OAuth 2.0 and Representational State Transfer (REST) architecture of the system implementation can also make SSO systems more secure. In its implementation, the use of an agile system development methodology with the Scrum framework is used to increase speed and flexibility. The results of this research show that the use of Google Identity, REST, and OAuth 2.0 can provide easy user access, guarantee access validity, accelerate client-server data exchange and simplify the SSO implementation process.